“Struktur Pertunjukan Tradisi Rateb Mensa di Kecamatan Beutong Ateuh Banggalang Kabupaten Nagan Raya”.: The Performance Structure of the Rateb Mensa Tradition in Beutong Ateuh Banggalang District, Nagan Raya Regency - Yulianti, Arisa; Denada, Berlian; Ocktarizka, Tria (LPPM ISBI Bandung, 2024)
This study formulates the problem of “The performance structure of the Rateb Mensa tradition in Beutong Ateuh Banggalang District, Nagan Raya Regency.” The research employed a qualitative method with a field research approach. The objective of this study is to describe the “Performance structure of the Rateb Mensa tradition in Beutong Ateuh Banggalang District, Nagan Raya Regency.” Research data were collected through observation, interviews, documentation, and triangulation/combined techniques. The theoretical framework used is the performance structure theory proposed by Djelantik, supported by Endraswara’s perspective. The results indicate that the performance structure of the Rateb Mensa tradition consists of three stages: pre-performance, main performance, and post-performance, presented in the form of group dhikr led by a Syeh (religious leader). The tradition is performed to enliven the Eid al-Fitr celebration and is carried out for three to four consecutive nights by male participants aged between 15 and 60 years. The number of performers ranges from 40 to 70 people, forming circular and shaf (row) formations. The Rateb Mensa chants include Al-Fatihah, Eid takbir, dhikr, shalawat, and laweut (poetic verses). This study demonstrates that preserving Rateb Mensa requires support in the form of documentation, regeneration, and revitalization through a community-based approach, ensuring it remains meaningful as a living intangible cultural heritage of Aceh rather than merely a spectacle.